2014
DOI: 10.1016/j.mod.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Novel expression of EGFL7 in placental trophoblast and endothelial cells and its implication in preeclampsia

Abstract: The mammalian placenta is the site of nutrient and gas exchange between the mother and fetus, and is comprised of two principal cell types, trophoblasts and endothelial cells. Proper placental development requires invasion and differentiation of trophoblast cells, together with coordinated fetal vasculogenesis and maternal vascular remodeling. Disruption in these processes can result in placental pathologies such as preeclampsia (PE), a disease characterized by late gestational hypertension and proteinuria. Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…Each qRT‐PCR was performed in triplicate with 25 ng cDNA. The relative expression levels of the target genes were calculated and expressed as fold change, 2 – ΔΔ Ct (51).…”
Section: Methodsmentioning
confidence: 99%
“…Each qRT‐PCR was performed in triplicate with 25 ng cDNA. The relative expression levels of the target genes were calculated and expressed as fold change, 2 – ΔΔ Ct (51).…”
Section: Methodsmentioning
confidence: 99%
“…The first observations that EGFL7 could control Notch signaling were made in neural stem cell cultures where it was found that the N-terminal half of EGFL7 specifically interacted with EGF domains in Notch1-4 and inhibited Notch signaling [40]. Subsequent work showed that EGFL7 control of Notch in endothelial and placental trophoblast cells was important for placenta development and that decreased EGFL7 expression may be linked to preeclampsia [41, 42]. In addition to controlling Notch via direct interaction with Notch receptors, recent work showed that RGD→RGE mutation of the EGFL7 integrin-binding domain enhanced Notch signaling in endothelial cells [32].…”
Section: Direct Ecm-notch Interactions That Control Notch Signalingmentioning
confidence: 99%
“…Placentas lacking transcriptional co-repressor Tle3 , a downstream effector of Notch signaling that is co-expressed with Notch2 in Ch-TGCs, have small, abnormally shaped venous channels [8]. In humans, expression of JAG1 is reduced in invasive TBs from women with preeclampsia [24] and expression of EGFL7, a modulator of NOTCH signaling, is reduced in preeclamptic placentas [25]. …”
Section: Introductionmentioning
confidence: 99%